(3hcGfJ gPg GdQbUI GdCNjQIs (3QhGjIs - (3GdLfOj, TQjfs ((3GdbGgQIs (3GdafGQs, 2024)
(3JYjT cGjdi QaQfS QGbUI GdHGdjI MjGI eKGdjI eY YGFdI QGFYI Edi Cf JfbdH MjGJgG QCkSG Ydi YbH HSHH ecGdeI gGJajI , dJLO faSgG aLCI hSW GdYOjO ef LQGFe GdbJd GdZjQ GdeHQQI CUHMJ cef jbOe YQkoVG QGbkUG dCTNGU eLghdjf agd jecfgG Cf JJQGbU eY cd Jdc GdUOeGJ , hJMGhd GdcTa Yf GdLGfjs
Keywords: (3GdbUU GdYQHjIs -- (3eUQs -- (3GdbQf GdYTQjfs